The effect of state antitakeover laws on the firm's bondholders - Francis, Bill B.; Hasan, Iftekhar; John, Kose; Waisman, Maya (Journal of Financial Economics, 2010)
We examine how state antitakeover laws affect bondholders and the cost of debt, and report four findings. First, bonds issued by firms incorporated in takeover-friendly states have significantly higher at-issue yield spreads than bonds issued by firms in states with restrictive antitakeover laws. Second, firms in takeover friendly states have significantly higher leverage than their counterparts in restrictive law states. Third, bond issues are associated with negative average stock price reactions among firms in takeover-friendly states, but positive stock price reactions among firms in restrictive law states. Fourth, existing bond values increase, on average, upon the introduction of Business Combination antitakeover law. These results indicate that state antitakeover laws tend to decrease bond yields and increase bond values, which is the opposite of their effect on equity values. This, in turn, implies that state laws help mitigate the agency cost of debt by shielding bondholders from expropriation in takeovers. Overall, the empirical evidence suggests that the effect of antitakeover provisions on firm value must take into account the impacts of both bondholders and stockholders.